Tailings recycling in the optimization of shotcrete at minera Cuzcatlan, Oaxaca - Mexico - Huaicane Mullisaca, Sergio Raúl (2023)
Mining companies generate tailings as a product of their metallurgical treatment, covering large amounts of land, generating pollution and hazards to the ecosystem, also, the optimization and increase of mining production is advancing rapidly being an important and worrying factor in this sector, because, in this specific case, it seeks to generate new alternatives to recycle this tailings and apply it in other activities, arising an opportunity to optimize the costs of support especially the cement used for the manufacture of shotcrete, since the high cost could take advantage of this tailings as a component of the concrete. To develop this research work, data collection techniques and the methodology of direct observation were used, because different types of physical-mechanical and petromineragraphic analysis were performed as a single component and in combination with the other elements of concrete; the results were encouraging, it was possible to integrate tailings into concrete and new mix designs were established, also, this work will generate lines of research to continue in the search for new applications of tailings in other activities of the sector.